(untitled) (ESMAT Magazine, 2021)
Since the 1990s, France has been engaged in a criminal policy of active counterterrorism. The objective of effectiveness and responsiveness requires the mobilization of special means of prosecution, repression and also prevention of terrorist action. In the light of the laws of 13 November 2014, 24 July 2015, 3 June 2016 and 30 October 2017, the analysis provides an overview of the anti-terrorist criminal policy conducted in recent years and the transformation of the fight undertaken - from a policy of action to anticipation of the terrorist phenomenon.